Establishment of faculty of veterinary medicine of university of selçuk and development within first ten years - Aşkın Yaşar (Eurasian Journal of Veterinary Sciences)
Veterinary Faculty of Selçuk University was established (By the force of 2547th. code of Higher Education Laws) in 1982. The faculty has shawed a good performance in development through first decade of its history.